Effectiveness the Use of Electronic Parking as the Implementation of Smart City in Semarang - Kinasih, Kania; Sri Rejeki, V.G; Tarigan, Riandi; Ardiyanto, A.; Sidharta, Albertus (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
In order to advance Semarang City, the Semarang City Government consistently strives to realize branding with the concept of a smart city. The most visible effort to implement smart cities is through electronic parking. The implementation of the smart city concept using electronic parking in Semarang City, one of which is located in the MT Haryono Street corridor. The purpose of this study is to find out the effective level of electronic parking as the application of smart city in Semarang City studied in the ERG theory of basic needs by Clayton Alderfer. The method used is a qualitative descriptive research approach through the need for the use of electronic parking, while data collection techniques through field observation, interviews, and documentation on location objects located in the MT Haryono Street Semarang City. The result of this study is that electronic parking in the MT Haryono corridor is not effective and is not the main factor in basic needs for Semarang residents. Semarang residents do not know much about the existence and feel the benefits of electronic parking. The government needs to socialize with residents about the existence and use of electronic parking.